Labor market frictions and spillover effects from publicly announced sectoral minimum wages - Gökay Demir (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
I analyze the spillover effects of publicly announced sectoral minimum wages in Germany. My identification strategy exploits exposure to sectoral minimum wages across workers and industries outside the minimum wage sector in a triple differences estimation. Subminimum wage workers in related industries outside of the minimum wage sector experience an increase in wages, job-to-job transitions, and reallocation from low-paying to high-paying establishments after the public announcement of Germany's first sectoral minimum wage. The reduction of information frictions, rather than the strategic interaction of employers, appears to be the main mechanism for these effects. When examining the spillover effects of other sectoral minimum wages from various contexts, I only discover positive spillover effects on sub-minimum wage workers in related industries outside the minimum wage sectors if the typical employment relationship in the minimum wage sector is comparable to that of the workers in my sample.
Keywords: J31; J38; J42; J62; 330; Spillover; labor market frictions; minimum wages; information frictions